EVALUASI FAKTOR EKONOMI MAKRO DALAM MEMPENGARUHI HARGA SAHAM - Slamet Ardi Restiawan; Rinda Asytuti (LPMP Imperium, 2020)
This study was used to determine the effect of macro economy on stock price of PT Telkom's. The condition of macro economic includes SBI, rupiah exchange rate, inflation, and also money supply. This type of research is quantitative using secondary data. The data taken is monthly closing of each variable, the sample used is saturated as much as 48 months. The data analysis method used is multiple linear regression analysis which previously met the classic assumption test requirements and also the hypothesis test. From the results of the analysis, it is known that SBI, rupiah exchange rate, inflation, money supply affect the stock price. Implications and suggestions are explained in the article